2007
DOI: 10.1051/0004-6361:20077873
|View full text |Cite
|
Sign up to set email alerts
|

Physical parameters of a mid-latitude streamer during the declining phase of the solar cycle

Abstract: Context. Investigating the physical properties of solar coronal streamers is important for understanding their role in the global magnetic structure of the extended solar atmosphere, as well as in the generation of the slow solar wind. Aims. We hope to contribute as completely as possible to the ongoing SOHO instruments campaign devoted to the study of the physical characteristics of coronal streamers at various heliocentric distances. Results. Electron densities and temperatures, H i and O vi kinetic temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
4
14
2
Order By: Relevance
“…We derive the H i temperature component T starting from the T ⊥ values obtained by the fitting procedure discussed in Sect. 2, and properly adopting the values of anisotropy found by Cranmer et al (1999) and Spadaro et al (2007). The results are shown in Figs.…”
Section: H I Temperature Anisotropymentioning
confidence: 64%
See 3 more Smart Citations
“…We derive the H i temperature component T starting from the T ⊥ values obtained by the fitting procedure discussed in Sect. 2, and properly adopting the values of anisotropy found by Cranmer et al (1999) and Spadaro et al (2007). The results are shown in Figs.…”
Section: H I Temperature Anisotropymentioning
confidence: 64%
“…5 as a function of the heliocentric distance. More recently Spadaro et al (2007) determined the physical parameters of a mid-latitude streamer during the declining phase of the solar cycle. They used a bi-Maxwellian distribution for the emitting ions in the Doppler dimming computation and found that the component of the H i temperature parallel to the magnetic field results in a factor of 1.3 smaller than the respective perpendicular component, independent of height (see Fig.…”
Section: H I Temperature Anisotropymentioning
confidence: 99%
See 2 more Smart Citations
“…In so doing, the solar wind outflow velocity turns out to be the only free parameter in the theoretical modelling of the Lyα intensity for the first time. It is worthwhile noting that in the past the extent of the streamer along the LOS has just been assumed (see Spadaro et al 2007;Susino et al 2008).…”
Section: Introductionmentioning
confidence: 99%